DEVELOPMENT OF STUDENTS’ SOCIAL THINKING AND SOCIAL COMPETENCE - Ilyorova O’lmasxon Maqsudjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes students’ social thinking and social competencies, social competence, socio-political and knowledge, the volume of specific knowledge, the development of ethical standards in society, the development of social competencies.